A Microstrip Sensor for Determination of Harvesting Time for Oil Palm Fruits - Abbas, Zulkifly (1994)
The conventional method to determine ripeness of the oil palm bunch is by using the number or percentage of detached fruits per bunch. However the method has the disadvantage that it does not relate to oil quantity and quality. Previous work has shown a close relationship between oil content and moisture content during fruit development. Thus,the oil content and subsequently the time to harvest the fruit bunch can be determined from moisture measurements. In this study, a microstrip sensor has been developed to determine the optimum time of harvesting the oil palm fruits based on microwave attenuation. The sensor operating at 10.7GHz was fabricated using RT-Duroidsubtrate and is suitable for single fruit measurements. A theoretical analysis has been carried out to predict the variation in at tenuati on with moisture content in the fruit mesocarp. The propagation of the electromagnetic wave in the microstripis based on quasi - transverse electromagnetic mode (TEM mode) and the at tenuation is obtained by using signal flow graph technique.